Efficacy of auricular acupoint pressing combined with acupoint massage in the adjuvant treatment of chronic obstructive pulmonary disease (耳穴压豆联合穴位按摩辅助治疗慢性阻塞性肺疾病的临床研究) - SONG Xueping (宋雪苹); GUO Yanbing (郭雁冰); LIU Jianqin (刘建琴); ZHAO Jiaying (赵佳莹); ZHANG Shuqi (张树琦); YU Juan (于娟) (中西医结合护理)
Objective To investigate the effect of auricular acupoint pressing combined with acupoint massage in the adjuvant treatment of chronic obstructive pulmonary disease (COPD). Methods A total of 80 COPD patients were randomly divided into the control group and observation group, with 40 cases in each group. Patients of the control group received routine treatment and nursing interventions such as monitoring illness condition, airway management, dietary guidance, psychological care and respiratory function exercise. Patients in the observation received auricular acupoint pressing combined with acupoint massage as adjuvant treatment for COPD. The lung function, Traditional Chinese Medicine symptom score, immune function, sleep quality, and quality of life before and after nursing were compared between the two groups, and patient satisfaction with nursing care was analyzed. Results Patients in the observation group had a better improvement in the forced expiratory volume in 1 s (FEV1), peak expiratory flow (PEF) and forced vital capacity (FVC) compared with those in the control group after implementation of nursing interventions(P＜0. 01). The Traditional Chinese Medicine symptom scores in the observation group were lower than those in the control group after nursing interventions(P＜0. 01). The level of CD3+ and CD4+, ratio of CD4+/CD8+ were significant higher in the intervention group than those in the control group(P＜0. 01). Scores of Pittsburgh Sleep Quality Index (PSQI) and COPD Assessment Test (CAT) were decreased more significantly in the observation group than those in the control group(P＜0. 01), and score of Leicester Cough Questionnaire(LCQ) was increased more significantly in the observation group than those in the control group(P＜0. 01). The satisfaction rate in the observation group was higher than that in the control group (P＜0. 05). Conclusion Auricular acupoint pressing combined with acupoint massage can effectively improve lung function and relieve clinical symptoms of COPD, improve patients' sleep quality and immune function, and enhance their quality of life during treatment. (目的 探讨耳穴压豆联合穴位按摩辅助治疗慢性阻塞性肺疾病(COPD)患者的效果。方法 选取2023年1月—2024年1月医院收治的80例COPD患者, 随机分为对照组和观察组, 各40例。对照组接受常规治疗和护理, 包括病情监测、呼吸道管理、饮食护理、心理护理和呼吸功能锻炼; 观察组在对照组基础上增加耳穴压豆联合穴位按摩。对比两组肺功能、中医症候积分、免疫功能、睡眠质量及生活质量改善情况, 评价护理满意度。结果 护理干预实施后, 两组第一秒用力呼气容积(FEV1)、呼气峰流速(PEF) 和用力肺活量(FVC)指标均较护理干预实施前改善, 且观察组改善优于对照组, 差异有统计学意义(P＜0. 01)。观察组中医证候积分改善优于对照组, 差异有统计学意义(P＜0. 01); 观察组免疫功能指标(CD3+、CD4+细胞比例和CD4+/CD8+)改善幅度优于对照组, 差异有统计学意义(P＜0. 01); 观察组匹兹堡睡眠质量指数(PSQI)、慢性阻塞性肺疾病评估测试(CAT)量表评分低于对照组, 莱斯特咳嗽问卷(LCQ)量表评分高于对照组, 差异有统计学意义(P＜0. 01)。观察组护理满意度高于对照组, 差异有统计学意义(P＜0. 05)。结论 在常规治疗的基础上, 耳穴压豆联合穴位按摩可有效改善COPD患者肺功能, 缓解临床症状, 提升睡眠质量及免疫功能, 提升生活质量。)